On the Well‐Posedness of Branched Transportation. Issue 4 (3rd June 2020) - Colombo, Maria; De Rosa, Antonio; Marchese, Andrea
Abstract : We show in full generality the stability of optimal transport paths in branched transport: namely, we prove that any limit of optimal transport paths is optimal as well. This solves an open problem in the field (cf. Open problem 1 in the book Optimal transportation networks by Bernot, Caselles, and Morel), which has been addressed up to now only under restrictive assumptions. © 2020 Wiley Periodicals LLC